Implementation of SAK-EMKM: The Influence of Socialization, Understanding Accounting and Readiness of MSMEs - Nurhani Patmawati; Devi Astriani; Trias Arimurti (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The objective of this study is to examine the impact of socialization, accounting comprehension, and readiness of micro, small, and medium enterprises (MSMEs) on the implementation of financial statement preparation based on the Indonesian Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK-EMKM). The research method is categorized as quantitative research. The study utilizes primary data in the form of a questionnaire. The study focused on the population of Micro, Small, and Medium Enterprises (MSMEs) that actively took part in the UMKM Juara program in the Karawang Regency during the year 2022. The sampling technique employed was saturation sampling, wherein the whole population under study was sampled. The utilized specimen had a value of 132. The findings indicated that partial socialization positively and significantly influences the implementation of financial statement preparation based on SAK-EMKM. On the other hand, an understanding of accounting has little impact on implementing financial statement preparation based on SAK-EMKM. Additionally, MSME readiness significantly affects the implementation of financial statement preparation based on SAK-EMKM. The concurrent processes of socialization, comprehension of accounting principles, and preparedness of MSMEs have a favorable and substantial impact on the execution of financial statement preparation based on SAK-EMKM.